2018
DOI: 10.2478/remav-2018-0011
|View full text |Cite
|
Sign up to set email alerts
|

Qualimetric Assessment of Investment Attractiveness of the Real Estate Property

Abstract: In this paper, an algorithm was proposed to define the integral quality coefficient of real estate (on the example of office centers) according to a property tree in the framework of qualimetric modelling. The aim of the paper is an attempt to apply qualimetric methods to evaluate the investment attractiveness of real estate property. When building a qualimetric model, information about the current state of the real estate market was gathered, and a survey of brokers and tenants of office centers was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Table 1 given below shows examples of new construction projects and the minimum prices for an apartment in a particular residential complex. According to the table, a studio apartment in one of the new residential complexes of the Ramenki district of Moscow will cost 2-3 million more than the cheapest lot in the secondary housing market of the same area, which indicates the increasing dynamics of price growth for new residential real estate after the introduced infrastructure changes, including transport [8,9]. Development of districts in the city center shows that good quality premium houses, in which the appropriate price level is maintained, enter the market only when the environment is largely formed (similar residential complex already exists) and when the conditions for a comfortable living are provided.…”
Section: Resultsmentioning
confidence: 99%
“…Table 1 given below shows examples of new construction projects and the minimum prices for an apartment in a particular residential complex. According to the table, a studio apartment in one of the new residential complexes of the Ramenki district of Moscow will cost 2-3 million more than the cheapest lot in the secondary housing market of the same area, which indicates the increasing dynamics of price growth for new residential real estate after the introduced infrastructure changes, including transport [8,9]. Development of districts in the city center shows that good quality premium houses, in which the appropriate price level is maintained, enter the market only when the environment is largely formed (similar residential complex already exists) and when the conditions for a comfortable living are provided.…”
Section: Resultsmentioning
confidence: 99%
“…The method of consistent dynamic quality assessment of production objects and processes proposed by the authors has been tested in conjunction with specialists in agriculture when conducting research in the agro-industrial sector [1,2]. The solution of the problems set is based on the theoretic and empirical research which uses the principles and techniques of standardization, system and situational modelling, qualimetric analysis [3], expert assessment and analysis, statistical methods, tabular and graphical methods of data conceptualization and interpretation [4,5].…”
Section: Methodsmentioning
confidence: 99%
“…Standard methods, such as the scenario approach (Cherepovitsyn et al, 2018), are widely used in investment design and in assessing the value of the object, using the income approach. In the works (Ozerov, 2007;Pupentsova & Livintsova, 2018), it was shown that, when choosing the best and most effective use of the object, uncertainty in the source data and in the predictions of their changes can lead to an erroneous choice. Creating scenarios for each use of the object will allow the selection of not only the criterion of income maximization (NPV, land value), but also the option with minimal risks (minimum coefficient of variation) (Nikolova et al, 2017;Bril et al, 2019).…”
Section: Methodsmentioning
confidence: 99%